"LIQUID BIOPSIES: TOOL FOR CANCER DIAGNOSIS AND MONITORING" - Ali Yahya Mater , Mohammed Ali Majari , Mohammed Ali Mohammed Anbari , Hassan Mohammed Ghabesh Ayashi , Afnan Mohammed Kulip Ali , Abdulqader Ali Ahmed Muthaffar ,Yahia Othman Ahmed Ghaish , Mohammed awadh almutairi , Walaa Abdulwahed Khalid , ,; Nouf Abdulqader Hassan , Mohammed Amer Asiri , Jameel Abdulrahman Alnemari , Fayez Saleem Aldhaferi , Maha Mohammed Moteq Almotairi , Fawaz Awad Zaben Alenazi, (Chelonian Research Foundation, 2022)
Liquid biopsy is a non-invasive technique that examines blood samples for circulating tumor indicators such as extracellular vesicles (EVs), cell-free DNA (cfDNA), and circulating tumor cells (CTCs). Liquid biopsy has several benefits over standard tissue biopsy, such as less invasiveness, the ability to detect tumor heterogeneity, and the ability to track the course of the disease in real time. While cfDNA conveys genetic variations for the purpose of discovering actionable mutations and tracking treatment response, CTCs shed from primary tumors and metastatic sites offer insights into tumor biology and metastatic potential and treatment response. EVs—exosomes in particular—contain molecular cargo indicative of the cell from which they originated, acting as extra biomarkers. However, there are obstacles in the way of liquid biopsy's extensive clinical application. Accurate analysis is hampered by technical constraints such low biomarker concentrations and the requirement for sensitive detection techniques. To guarantee repeatability across laboratories, pre- and analytical procedure standardization is crucial. Its usefulness in the early identification of cancer is still limited, necessitating meticulous assay validation to reduce the number of false-positive and false-negative results. Notwithstanding these obstacles, research is still being done to improve liquid biopsy methods. Extensive prospective studies are being conducted to verify its prognostic and predictive use in monitoring the course of the disease and directing treatment choices. Liquid biopsy has the potential to revolutionize individualized cancer therapy by offering real-time insights into tumor dynamics and therapeutic responses, provided that it is rigorously validated and advances technologically. Key words: Liquid biopsy, Free DNA, Circulating tumor cells, tumor, diagnosis.